KAZAKHSTAN: HOW ITS MULTIPARTY SYSTEM CAME INTO BEING - BABAK, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2005)
The discussion clubs, political circles, etc. which appeared in Kazakhstan (and elsewhere across the country) during Gorbachev’s perestroika laid the foundation of political parties as an indispensable attribute of any democratic society. In Kazakhstan, however, the process acquired its specific features because of the geographic lo cation of the entire Central Asian region, the past of its variegated population, and its ethnic composition. Along with the general crisis that had enveloped the Soviet Union, the events of December 1986 in Alma Ata, when the youth openly moved against the Soviet practice of appointing the republic’s top Communist and state leaders by the Kremlin, were an important factor which sped up the emergence of these quasi-political organizations in Kazakhstan. The rally and the use of force to suppress it echoed throughout the republic and be yond. The pernicious ecological effects of the tests at the Semipalatinsk nuclear test ground and some other military objects which have been made public also raised political awareness among the Kazakhstanis. It was on a grass-roots initiative that the first informal political organizations appeared in the republic. Under conditions of a deepening economic and social crisis and weakened control over public sentiments, the so-called dissidents, especially from among the students, became more eloquent about the state of affairs in the country and quite frank about its future. Their discussions led them further away from the official line. In October 1988, a public organization, the Alma Ata Popular Front, was created; in December, a historical-educational club called Akikat (the Truth) was set up. In December of the same year, historical-educational groups (which were in fact branches of the All-Union Anti-Stalinist Memori al Society) appeared in Tselinograd (today Astana) and Alma Ata and became fairly popular. The Memorial was engaged in rehabilitating the victims of the Stalinist repressions, helping those who survived and the relatives of those who perished in the camps, and fighting the remnants of totalitarianism in public consciousness. The authorities of still Soviet Kazakhstan tried to split the Memorial movement by setting up its twin structure called Adilet (Justice), formally pursuing the same aims, with branches in Karaganda, Dzhezkazgan, Chimkent, and other cities. The powers that be tried to set the Memorial members (mainly politically aware intelligentsia of European origin) and the Adilet members, who were mainly Kazakhs, against each other. While at the first stage, the Russians and Russian speakers of Kazakhstan limited their political activity mainly to political clubs, the young Kazakhs expressed their political convictions and dis satisfaction with the political and economic realities in more active protest forms: occupation of landed plots on a mass scale to build housing for themselves (this happened, in particular, in Alma Ata in the summer of 1990). These people united into societies Shanyrak, Daryn, and Altyn besik. Early in 1990, the still ruling Communist Party initiated youth structures under its aegis of the Kazak tili (the Kazakh Language) type; very soon more youth national-democratic organizations appeared. The largest of them outside Alma Ata was the Chimket Union of Independent Kazakh Youth. Like in many other regions of the former Soviet Union, structures and movements officially engaged in environmental protection also appeared in Kazakhstan. The first emerged in 1987 (in Pavlodar, in particular). At that time, an alliance called Initsiativa was set up in the society of environmental protection of Alma Ata; in November a Public Committee for the Problems of Lake Balkhash and the Aral Sea came into being. In 1988, the green movement gained even more strength; Taldy-Kur gan, Djambul and Chimkent acquired ecological organizations. In June 1988, all the corresponding organizations of Alma Ata united into the so-called Green Front. 1 Most of them, with their membership of mainly Russian-speaking intelligentsia, were small. Very soon, their political ideas became obvious and made them even more attractive to the youth.